2015
DOI: 10.1016/j.amepre.2015.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Leader Behaviors, Group Cohesion, and Participation in a Walking Group Program

Abstract: Background Fewer than half of all U.S. adults meet the 2008 Physical Activity Guidelines. Leader behaviors and group cohesion have been associated with increased participation or adherence in sports team and exercise class settings. Physical activity interventions in community settings that encompass these factors may enhance intervention adherence. Purpose To examine the impact of Community Health Promoter leader behaviors and group cohesion on participation in a walking group intervention among racially/et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 39 publications
4
22
1
7
Order By: Relevance
“…For example, Walking for Health has approximately 70,000 participants across the UK [73], and 5045 adults were exposed to walking groups across the 14 identified intervention studies. When we examined reach across PROGRESS-Plus characteristics, however, walkers were predominantly women [37,45,46,50,53,56,59,75,76,78,82,89,90], white [43,46,75,76,89], socioeconomically advantaged [38,46,71,72,75,77] and mid-to-older aged [15,20,40,46,49,53,55,59,75,76,90]. Overall, our assessment corroborated previous findings [6,7,19,20], and contrasted with Ball et al's recent conclusions [5].…”
Section: Reachsupporting
confidence: 84%
See 3 more Smart Citations
“…For example, Walking for Health has approximately 70,000 participants across the UK [73], and 5045 adults were exposed to walking groups across the 14 identified intervention studies. When we examined reach across PROGRESS-Plus characteristics, however, walkers were predominantly women [37,45,46,50,53,56,59,75,76,78,82,89,90], white [43,46,75,76,89], socioeconomically advantaged [38,46,71,72,75,77] and mid-to-older aged [15,20,40,46,49,53,55,59,75,76,90]. Overall, our assessment corroborated previous findings [6,7,19,20], and contrasted with Ball et al's recent conclusions [5].…”
Section: Reachsupporting
confidence: 84%
“…Literature showed that outdoor walking groups resulted in increased physical activity (according to both objective and subjective measures) and numerous health benefits, with negligible negative outcomes. These benefits were both physical and psychological, and included increased physical fitness [50]; decreased hypertension and positive changes in blood lipoproteins [37,60,71,82]; decreased breathlessness [52]; increased self-efficacy and relaxation [77]; and reductions in depression [38] and anxiety [50]. Thus, our findings largely support previous reviews [6,7].…”
Section: Evidence Of Effectivenesssupporting
confidence: 83%
See 2 more Smart Citations
“…Evidence in our targeted searches also suggested that the real or perceived skill of the activity leader were instrumental in ongoing Adherence, these include: psychological support (Estabrooks et al, ; Izumi et al, ), motivational capacity (Caperchione, Mummery, & Duncan, ), trust (Estabrooks et al, ; Izumi et al, ), and promoting a positive environment (Estabrooks et al, ; Izumi et al, ).…”
Section: Resultsmentioning
confidence: 82%